Spreadsheet simulation for industrial application: a case study - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba (2009)

(untitled)
The paper reports and demonstrates the spreadsheet simulation that used for production planning and inventory control in a composite based product manufacturer. It covers the development of the spreadsheet simulation template and the application. The findings show that the application of the spreadsheet simulation positively improve the time to estimate the production lead time, and monitoring activities on material usage included raw material, chemical and ancillary. Besides, it provides well-managed documentations for production planning and control.